Scientific Productivity of Polymer Science Research: A Scientometric Study - Hadagali, Gururaj S.; Kumbar, B. D.; Keshava (Journal of Information and Knowledge, 2014)
The present study discusses the scientific productivity of polymer science research as reflected in J-Gate for the period from 2000-2009. This study investigates the authorship pattern, geographical distribution of contributors, highly productive authors, highly preferred journals by the scientists, sectoral distribution, Degree of Collaboration (DC) and Collaborative Co-efficient (CC) and growth pattern of polymer science research by calculating relative growth rate and doubling time for publication.